Remote Adipose Tissue-Derived Stromal Cells of Patients with Lung Adenocarcinoma Generate a Similar Malignant Microenvironment of the Lung Stromal Counterpart. (24th January 2023) - De Falco, Elena; Bordin, Antonella; Menna, Cecilia; Dhori, Xhulio; Picchio, Vittorio; Cozzolino, Claudia; De Marinis, Elisabetta; Floris, Erica; Maria Giorgiano, Noemi; Rosa, Paolo; Angelo Rendina, Erino; Ibrahim, Mohsen; et al.
Abstract : Cancer alters both local and distant tissue by influencing the microenvironment. In this regard, the interplay with the stromal fraction is considered critical as this latter can either foster or hamper the progression of the disease. Accordingly, the modality by which tumors may alter distant niches of stromal cells is still unclear, especially at early stages. In this short report, we attempt to better understand the biology of this cross-talk. In our "autologous stromal experimental setting, " we found that remote adipose tissue-derived mesenchymal stem cells (mediastinal AMSC) obtained from patients with lung adenocarcinoma sustain proliferation and clonogenic ability of A549 and human primary lung adenocarcinoma cells similarly to the autologous stromal lung counterpart (LMSC). This effect is not observed in lung benign diseases such as the hamartochondroma. This finding was validated by conditioning benign AMSC with supernatants from LAC for up to 21 days. The new reconditioned media of the stromal fraction so obtained, was able to increase cell proliferation of A549 cells at 14 and 21 days similar to that derived from AMSC of patients with lung adenocarcinoma. The secretome generated by remote AMSC revealed overlapping to the corresponding malignant microenvironment of the autologous local LMSC. Among the plethora of 80 soluble factors analyzed by arrays, a small pool of 5 upregulated molecules including IL1- β, IL-3, MCP-1, TNF- α, and EGF, was commonly shared by both malignant-like autologous A- and L-MSC derived microenvironments vs those benign. The bioinformatics analysis revealed that these proteins were strictly and functionally interconnected to lung fibrosis and proinflammation and that miR-126, 101, 486, and let-7-g were their main targets. Accordingly, we found that in lung cancer tissues and blood samples from the same set of patients here employed, miR-126 and miR-486 displayed the highest expression levels in tissue and blood, respectively. When the miR-126-3p was silenced in A549 treated with AMSC-derived conditioned media from patients with lung adenocarcinoma, cell proliferation decreased compared to control media.